Estudos dos efeitos de metaloproteases/desintegrinas isoladas do veneno da serpente Bothrops alternatus sobre a adesão celular e a expressão gênica - Cominetti, Márcia Regina (2004)
This work presents the isolation and biological characterization of a novel metalloprotease/disintegrin, BaG, isolated from the Bothrops alternatus snake venom. BaG was purified in a two-step chromatographic model using Gelatin-Sepharose and DEAE-Sepharose resins. The molecular mass of purified protein was estimated by SDS-PAGE as approximately 130kDa under non-reducing conditions and 55kDa under reducing conditions. This result suggests a dimeric structure for BaG. BaG shows proteolytic activity on casein, which was inhibited by EDTA. This protein did not induce any hemorrhage when applied intradermally in mice at doses up to 10µg. 1,10-phenanthroline-treated BaG (BaG-I) inhibits ADPinduced platelet aggregation with an IC50 of approximately 180nM. BaG-I also inhibits fibronectina-mediated cell adhesion with an IC50 of 3.65µM. K562 cells bind to BaG-I probably though interaction with integrin α5β1, since anti-α5β1 antibodies inhibited K562 cell adhesion to BaG-I. BaG-I also induces the detachment of K562 cell previously bound to fibronectin and decreases the number of viable K562 cells after 24, 48 and 72h of incubation. In the second part of this work, gene expression analyses in human fibroblasts treated with alternagin-C (ALT-C) were carried out. ALTC is a disintegrin-like/cysteine-rich protein isolated from the venom of B. alternatus. This protein induces the expression of various cell signaling- and cell proliferation-related genes including VEGF, which was confirmed by ELISA analysis. This induction could explain some previous results showing that ALT-C stimulates cell proliferation in endothelial cells.